A ruptured seventeen weeks’ ectopic pregnancy: a case report - Usama Shabbir; Jamal Anwar; mohammad Sohail Asghar; Balakh Sher Zaman; Ameer Afzal; Mussab Nadeem (Journal of the Pakistan Medical Association, 2020)
Abstract Ectopic pregnancy is a common condition with a prevalence of 2% in all pregnancies. Implantation of the developing blastocyst outside the uterine cavity leads to ectopic pregnancy. About 95% of ectopic pregnancies occur in the different segments of the fallopian tubes. Usually, an ectopic pregnancy grows up to 1.5–3.5 cm and any size greater than this leads to rupture. We present a case of ruptured ectopic pregnancy in which the foetus had a crown–rump length(CRL) of 12 cm was retrieved. To our knowledge, this is the largest foetus recovered from a ruptured ectopic pregnancy at the ampulla of fallopian tube reported in the literature. Timely diagnosis and proper management is the key to reduce morbidity associated with it. Keywords: Ectopic pregnancy Hemoperitoneum Implantation Continuous...